2017
DOI: 10.1161/circgenetics.116.001498
|View full text |Cite
|
Sign up to set email alerts
|

Functional Validation of a Common Nonsynonymous Coding Variant in ZC3HC1 Associated With Protection From Coronary Artery Disease

Abstract: Background— Although virtually all coronary artery disease associated single-nucleotide polymorphisms identified by genome-wide association studies (GWAS) are in noncoding regions of the genome, a common polymorphism in ZC3HC1 (rs11556924), resulting in an arginine (Arg) to histidine (His) substitution in its encoded protein, NIPA (Nuclear Interacting Partner of Anaplastic Lyphoma Kinase) is linked to a protection from coronary artery disease. NIPA plays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
0
15
1
Order By: Relevance
“…In fact, in the course of our experiments, initially all performed with cells in which ZC3HC1 had been knocked down by RNAi, we had realised that this protein was most likely neither essential for cell cycle progression nor cellular housekeeping activities in interphase (Figure S14). However, even though these early results turned out to be in accordance with the finding that mice in which the ZC3HC1 gene had been knocked out by homologous recombination are viable [104,105], the alleged role for ZC3HC1 in regulating cell cycle progression via controlling cellular levels of CCNB1 was recurrently reported to manifest itself in a range of aneuploid human tumour cell lines and other types of immortalised human cells [104,[106][107][108]. HeLa cells were actually suggested to be amongst those cells in which such ZC3HC1 knockdown phenotypes were most pronounced [104], ranging from most cells of a ZC3HC1-deficient HeLa population being no longer capable of cell cycle progression and entering apoptosis instead [104], to hyperproliferation of another ZC3HC1-deficient HeLa population and conspicuous increase in its cell numbers [108], when using the one or other ZC3HC1 siRNA.…”
Section: Zc3hc1 Is Not Required For Cellular Housekeeping Activities In Human Tumour and Non-tumour Cell Lines Of Ectodermal Mesodermal Amentioning
confidence: 67%
“…In fact, in the course of our experiments, initially all performed with cells in which ZC3HC1 had been knocked down by RNAi, we had realised that this protein was most likely neither essential for cell cycle progression nor cellular housekeeping activities in interphase (Figure S14). However, even though these early results turned out to be in accordance with the finding that mice in which the ZC3HC1 gene had been knocked out by homologous recombination are viable [104,105], the alleged role for ZC3HC1 in regulating cell cycle progression via controlling cellular levels of CCNB1 was recurrently reported to manifest itself in a range of aneuploid human tumour cell lines and other types of immortalised human cells [104,[106][107][108]. HeLa cells were actually suggested to be amongst those cells in which such ZC3HC1 knockdown phenotypes were most pronounced [104], ranging from most cells of a ZC3HC1-deficient HeLa population being no longer capable of cell cycle progression and entering apoptosis instead [104], to hyperproliferation of another ZC3HC1-deficient HeLa population and conspicuous increase in its cell numbers [108], when using the one or other ZC3HC1 siRNA.…”
Section: Zc3hc1 Is Not Required For Cellular Housekeeping Activities In Human Tumour and Non-tumour Cell Lines Of Ectodermal Mesodermal Amentioning
confidence: 67%
“…Because eQTL effects are often cell type specific, we tested whether an eQTL was present in aortic SMCs from 151 heart transplant donors 16 , finding that SMCs from donors carrying the rs11556924-T allele have lower ZC3HC1 expression and migrate faster than SMCs from donors carrying the rs11556924-C allele. The absence of a significant association between ZC3HC1 expression and rs11556924 in blood samples 9 , monocytes/macrophages 28 and aortic endothelial cells 29 suggests that the regulatory impact of the variant at the ZC3HC1 locus is specific to SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitously expressed ZC3HC1 gene encodes the cell cycle protein NIPA, which has been found first to be associated with CAD in several independent GWASs [2][3][4][5][6][7][8] . The CADassociated rs11556924-C/T SNP in ZC3HC1 is functional, leading to an amino acid change from arginine to histidine (p.Arg363His) 4,7,9 . Analysis of the publicly available GTEx dataset eQTL (V8) showed that the genetic variant rs11556924-T results in reduced ZC3HC1 gene expression in heart (atrial appendage and left ventricle) and skin samples.…”
Section: Knockout Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In functional studies, we demonstrated that the ensuing cellular phenotype of the protective variant is one of increased NIPA expression and nuclear mobility and lower rates of cell growth. 67…”
Section: From Locus To Functionmentioning
confidence: 99%